Enhancing Indonesian Students’ Self-confidence through the Integration of Problem-based Learning (PBL) and Technology - Pasttita Ayu Laksmiwati (Southeast Asian Mathematics Education Journal, 2018)
Access to technology in learning is important and is essential in facilitating students’ use of technology in their learning process. The aim of this study was to enhance students’ selfconfidence with Pythagoras’ Theorem by using problem-based learning (PBL) and technology. The technology used was GeoGebra. This study was conducted at a state junior secondary schools in Indonesia. The researcher employed an action research methodology. Twenty-four second year students (12 boys and 12 girls) from the juniorsecondary school participated in this study. The sampling technique used was purposive random sampling. This study used a pre-experimental design with no control group with both qualitative and quantitative data collected and analysed. There were two cycles in this action research. The investigation showed that the integration of problem-based learningand technology has positive impacts on sample students’ self-confidence. The students’ mean score, which was 80.54 (average self-confidence) on the pre-test, showed an improvement in the post-test with 106.13 (high self-confidence). In addition, the researcher conducted interviews of three students. The result showed that the learning had as positive impact on the students’ self-confidence. As part of 21st century society, students need tosurvive in the workplace and teachers can play their role in accomplishing this in the teaching and learning process. While the researcher cannot make generalisations due to the nature of the sample, nevertheless the integration of problem-based learning and technology in the mathematics learning process will be of interest to teachers and educators looking to improve their students’ self-confidence.